Rice growth and the associated phosphate solubilizing bacteria on an Alfisol treated with insecticide and endophytes inoculum - Shofiyah, Laily; Sudadi, Sudadi; Cahyani, Vita Ratri (Brawijaya University, 2025)
The long-term use of excessive amounts of chemical fertilizers and pesticides adversely affects soil fertility, crop productivity, and biodiversity of soil and endophytes microbes. This study evaluated the ability of endophytic bacteria isolated from rice plants to enhance soil fertility, promote plant growth, and induce rice plant resistance on Alfisols treated with insecticide 10x usage dose (chlorantraniliprole 100 g L-1 and thiamethoxam 200 g L-1), and also assessed the diversity and population density of the associated phosphate solubilizing rhizospheric and endophytic bacteria. Three isolates of Burkholderia sp. YErOI-1 (I1), Bacillus sp. NErOI-2 (I2), Burkholderia sp. PElOI-3 (I3) and a mixture of three isolates (I4) were tested in combination with (P1) and without (P0) insecticide treatments in the pot cultivation of rice Inpari 32 using Alfisols in a completely randomized factorial design with three replications. The results showed that the control (I0P0) demonstrated higher plant growth compared to I0P1, indicated insecticide treatment resulted in toxicity effect. Among all the treatments, I2P0, I2P1, and I1P0 yielded the highest plant growth, whereas the lowest was indicated by I1P1. The rice associated phosphate solubilizing rhizospheric and endophytic bacteria indicated the highest population density and diversity index on the treatments I3P0 and I3P1 which significantly correlated with the highest P concentration and P uptake in these two treatments. Isolate I2 showed the strongest effect in inducing plant growth to insecticide resistance, in contrast isolate I1 showed no support in inducing plant resistance to insecticide. Further study is needed to examine the effect of the present assessed endophytes in other type of pesticide treatments.